Comparative Study on River Manufactured and Rock Sand on the Compressive Strength of Concrete Grade-25. - Rukundo, Patrick (Kabale University, 2024)
The compressive strength of concrete is the strength of hardened concrete, which is the measure of the concrete’s ability to resist loads that tend to compress it without cracking or deformation. Duff Abrams revealed that the strength of a concrete mix is solely dependent on the mass of water compared with that of the cement. It is noted that compressive strength does not only depend on water-cement ratio but also on some other factors such as cement strength class and fineness, concrete age, duration of curing, admixtures, and aggregate properties such as size, shape, texture, and strength. This study was aimed at assessing the effect of different particle sizes of fine aggregates (river, rock , and manufactured sand) on concrete properties. It was found that the concrete compressive strength at 28 curing age increased with the increase in the percentage replacement aggregates that is; for river sand replacement with rock sand 25.2, 25.5, 26.1, 26.7, and 27.3 MPa for 0, 25, 50, 75 and 100% and for stone dust replacement with river sand 25.2, 27.7, 27.0, 28.6 and 28.7Mpa for 0, 25, 50, 75 and 100%.